Association between Lactation Massage and Breast Milk Production among Postpartum Mothers: A Quasi-Experimental Study in a Primary Healthcare Setting - Ronni Naudur Siregar; Eva Hotmaria Simanjuntak; Netti Meilani Simanjuntak (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Adequate postpartum milk output is critical for achieving exclusive breastfeeding. Delayed or inadequate breast milk production frequently results in early formula feeding and interruption breastfeeding exclusivity practices. Lactation massage is a complementary non-pharmacological technique thought to stimulate the production of oxytocin and prolactin hormones, which may contribute to breast milk production. Objective: The present study aimed to investigate the correlation between lactation as well as breast milk production among postpartum mothers. Methods: This study design a quasi-experimental non-equivalent control group and pretest–posttest assessment, conducted without randomization at Pratama Salbiyana Clinic, Medan Deli, Indonesia, from October 2024 to April 2025. Total of 20 postpartum women were recruited through total sampling and split into two groups: 10 Each group consisted of 10 participants. The provided group received with lactation massage daily for three consecutive days (on postpartum days 2 to 4), Meanwhile, the provided control group was given standard postpartum care. without massage. Breast milk output was evaluated both before and after the intervention through direct expression and measurement of volume (in cc) in field conditions, and results were categorized using predetermined criteria Wilcoxon signed-rank and Mann–Whitney tests were used (p < 0.05). Results: Findings indicated that the proportion of mothers producing higher amounts of milk production from 30% at baseline to 90% following the intervention. The Wilcoxon signed-rank test showed a significant improvement before and after lactation massage (p = 0.014), and considerable difference was observed between the intervention and control groups (p = 0.029). However, the results interpreting with caution as the small sample limited, absence of randomization, and possible inconsistencies in measurement conditions. Conclusion: Lactation massage may be associated with increased Postpartum mothers' production of breast milk. These findings provide preliminary, context-specific evidence and should be interpreted cautiously. Further studies with larger sample sizes, randomized study designs, and standardized measurement methods protocols are needed to confirm these findings.